Shelf Life and Quality Attributes Of Fresh Beef Infused With Organic Acids. - Mohamed Saeed, Mohamed Abd Elgadir (2005)
Fresh beef is a highly perishable food. It has a shelf life of one day at ambient temperature and a few days at refrigerated temperature. This study was conducted with the objective of extending the shelf life of fresh beef by infusing organic acids such as citric, tartaric, acetic and lactic acids, and combination of the organic acids with sodium chloride. Fresh beef (longissmus do@ purchased from the local market were sliced and were infused with citric, acetic, lactic and tartaric acids in concentration of 0.5%, 0.75% and 1 %, and combination of 1.00% of citric and acetic acids with and without sodium chloride by placing samples in vacuum desiccators and pulling the vacuum to 29.5 in. Hg. for 20 min.,. All samples were packed in vacuum packs (22 (L) x 18 (w) crn. and stored at S°C for 28 days. pH, A, Total Plate Count (TPC), Thiobarbaturic acid values, Hunter colour values , instrumental texture, proximate composition were determined. The pH values of treated samples dropped from the initial pH of 5.30 (untreated) to 4. 20 - 4. 47 and upon storage, the pH values of all sampies increased gradually. The TPC values were lower than 10' CFUlg on day 16, 20 and 28 in samples treated with 0.5%, 0.75% and 1.00% acids, respectively. The proximate com p s iti on of treated samples was affected by infusion process. The instrumental texture of fresh beef was harder upon treatment. The maximum shelf life of treated beef was 12 - 24 days for samples treated with 0.5% of all acids, 16 - 24 days for samples treated with 0.75% and 20 - 28 for samples treated with 1.00%. Citric acid in concentration of 1.00% gave the best effect which was followed by acetic acid. In citric and acetic acids and citric and acetic acids with sodium chloride combinations, the later in the ratio of 2:1 was more effective in decreasing the initial pH of fresh beef immediately after infusion. Increasing concentration of NaCl in the infusion solution resulted in the smaller decrease in the pH values. The TPC value was observed in samples treated with 2:1 citric: acetic acids. The growth of S.aureus and E.coli 0157:H7 were significantly (B0.05) decreased by 0.85 loglo and 0.73 logto, respectively. The initial thiobarbituric acid value in untreated fresh beef was 0.735 mg MDNkg which significantly (pc 0.05) decreased in all treated samples. At the end of storage study, lowest TBA values were obtained in samples treated with 2:l citric and acetic. The increase in the addition of NaCl caused a parallel increased in TBA values. For colour, Hunter 'b' and 'L' values increased with storage time while 'a' decreased significantly (R0.05). The processed beef burger during chilled storage had a storage life of 8 days.